THE ROLE OF ATTENTION IN VISUAL AWARENESS - Colmenero Jiménez, José María (Anales de Psicología / Annals of Psychology, 2004)
The main purpose of this article is to review the most relevant results about relations between attention and visual awareness. More specifically, we examine classic and more recent work related with actual theories about the attentional mechanism. We also review the main results about the relevance of conscious processing and the work centred on the neural correlates of visual awareness. Most prominent models about the role of attention and consciousness are also considered. In sum, all this sort of evidence clearly shows that attentional networks are specifically implicated in different levels of consciousness.